Balancing significant cost cutting and maintaining profitable operations in a cost reduction exercise. A case of Mega Pak (Pvt) Ltd - Nyasulu, Martryona (2017)
The study was carried out to find ways to balance significant cost cutting while maintaining profits in a cost reduction exercise of Mega Pak (Pvt) Ltd. The need for the research emanated from the company’s total costs that were rapidly increasing as well as the projected decline in profits and increase in costs as a result of price controls that were instituted by Delta, the company’s major shareholder and customer which contributed 55% of the company’s revenue. The research method used was a case study and questionnaires and interviews were used as primary data gathering instruments and financial statements were used as secondary data. The sample size used consisted of 33 respondents of which 26 responded to questionnaires and 7responded to interviews. Tables were used to present data gathered and graphs, pie charts and bar charts were used to analyse data and interviews were summarised. The major findings of the study showed that the company was not utilizing all the cost reduction strategies that were reviewed by other authors, scholars and journals. Theoretical views were used alongside findings to provide recommendations to Mega Pak (Pvt) Ltd. The research recommended the adoption of the ABC costing and lean production, continuation of energy saving through use of filters, replacement of wooden pallets with plastic pallets and collection of used plastic bottles for use in recycling as it will significantly cut costs. The research further recommended introduction of new products from the recycled material as a way of increasing revenue, hence increasing revenue base of third party customers and profits.